ASSESSING OF PREGNANT WOMEN TOWARD VAGINAL DELIVERY AND CESAREAN SECTION BASED ON BEHAVIOURAL INTENTION MODEL - Dr. Hani Baloch; Dr Yamina Ishtiaq; Dr Kausar Parveen; Dr Ayesha Basharat; Dr Sadia Kanwal; Ulfat Naseem; Dr Gulnaz; Sana Mukhtiar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: The decision-making process surrounding childbirth method, whether vaginal delivery or cesarean section, is a complex interplay of medical, psychological, and sociocultural factors. Objectives: The main objective of the study is to find the behavior of pregnant women toward vaginal delivery and cesarean section based on behavioural intention model. Material and methods: This quantitative study was conducted at Bolan Medical Complex Hospital Quetta March 2022 to March 2023. Data was collected from 220 pregnant women.Data collection involved structured interviews conducted with pregnant women in their third trimester of pregnancy. Participants were recruited from antenatal clinics in various healthcare facilities, following the application of inclusion and exclusion criteria. Prior to data collection, informed consent was obtained from each participant. Results: Data were collected from 220 pregnant females.Mean age of participants was 28.01±3.5 years. There were 120 (54.5%) females was in primigravida group and 100 (45.5%) was in multigravida. 150 (68.2%) adopt vaginal delivery and 70 (31.8%) adopt C-section.Attitudes exhibited the strongest predictive power, with a beta coefficient of 0.45 and a highly significant p-value of <0.001, followed by subjective norms (β = 0.32, p = 0.002) and perceived behavioral control (β = 0.28, p = 0.005). Collectively, these predictors accounted for 65% of the variance in pregnant women’s intentions toward childbirth methods, as indicated by the R-squared value. Conclusion: It is concluded that pregnant women exhibit strong positive attitudes toward natural childbirth, while expressing reservations about cesarean section (CS). These findings highlight the importance of patient-centered care in prenatal settings, where healthcare providers should prioritize addressing women’s preferences and concerns.